2021
DOI: 10.1186/s12872-021-02390-y
|View full text |Cite
|
Sign up to set email alerts
|

Does body mass index or waist-hip ratio correlate with arterial stiffness based on brachial-ankle pulse wave velocity in Chinese rural adults with hypertension?

Abstract: Background The relationship between obesity indices and arterial stiffness (AS) has not been fully discovered nor has it been studied in depth in large hypertensive patient populations. The aim of this study was to explore the association between body mass index (BMI) and waist-hip ratio (WHR) levels and AS based on brachial-ankle pulse wave velocity (baPWV) in Chinese rural adults with hypertension. Methods This cross-sectional study analyzed 5049… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Many clinical studies indicated that BMI is positively associated with increased PWV (12, 13). However, several studies suggested that BMI is negatively associated with high arterial stiffness (15,16). Moreover, Liao et al conducted a longitudinal study of 1553 subjects found that there was no relationship between the BMI and AS after correction for SBP and DBP (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical studies indicated that BMI is positively associated with increased PWV (12, 13). However, several studies suggested that BMI is negatively associated with high arterial stiffness (15,16). Moreover, Liao et al conducted a longitudinal study of 1553 subjects found that there was no relationship between the BMI and AS after correction for SBP and DBP (18).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, current researches are still controversial about the relationship between BMI and AS among different populations. In the past decade, some studies have found a positive association between BMI and AS (12-14), while others have found a negative association (15,16), and others have found no association (17,18). These discrepancies between the different studies may be attributed to different sample sizes, ethnic and regional variations.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the results of the two-way ANOVA and the unconditional logistic regression models showed that hypertension was statistically significant in both baPWV and arteriosclerosis, which may suggest that hypertension is a crucial factor influencing arteriosclerosis. Approximately 23.2% of adults in China are estimated to suffer from hypertension, which is often accompanied by obesity (F. Hu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…arteriosclerosis, which may suggest that hypertension is a crucial factor influencing arteriosclerosis. Approximately 23.2% of adults in China are estimated to suffer from hypertension, which is often accompanied by obesity (F. Hu et al, 2021). We set the OR value of normal (BMI and blood pressure) participants to 1 as a reference in the unconditional logistic regression model to identify whether an interaction between obesity and hypertension affects the occurrence of arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Esmaillzadeh et al concluded that WHR was a better screening measure for cardiovascular risk factors, especially HTN, than other anthropometric indices in adult men [ 20 ]. Evidence suggests that WHR is positively correlated with arterial stiffness [ 36 ], which plays a significant role in the pathogenesis of HTN and can predict the likelihood of cardiovascular events in hypertensive patients [ 37 ]. Moreover, excess abdominal fat deposition causes high-density lipoprotein (HDL) levels to decrease, and low-density lipoprotein (LDL) and triglyceride levels to increase, and a high LDL level is a well-established risk factor for HTN [ 38 ].…”
Section: Discussionmentioning
confidence: 99%